STUDI RELE DIFFERENSIAL PADA TRAFO INTERBUS DI GARDU INDUK TEGANGAN EKSTRA TINGGI GANDUL - Agung Hariyanto; Oktaria Handayani; Daru Kurniawan (Sutet, 2016)
Transmit power, Substation electrical components have a Parent in the form of a power transformer for transforming electrical power, by changing the magnitude ofvoltage while frequency remains. One of its kind based on the voltage i.e. transformer 500/150 kV and 150/70 kV Interbus commonly referred to as Transformer (IBT).Transformer is the heart of the distribution and transmission of which is expected to operate at maximum. In order to function properly, then the transformer must be kept andcared for properly using the proper equipment and systems. As the State-owned electricity company, PT PLN (Persero) trying to supply electrical energy optimally. To maintain thequality of the electrical energy is transmitted, system security and maintenance of the electrical equipment of a much needed parent booths. If the transformer is experiencinginterference, then the distribution of electric power can be interrupted, so a transformer requires protection equipment. On the transformer often experience internal disturbancesso that the main safeguards are required i.e. differential relay useful to secure the entanglement of the transformer in case of a disruption. Rele is very selective and worksso quickly that the system can isolate the internal disorder as quickly as possible without resulting in further damage.